POLC SEBAGAI STRATEGI SDM DALAM PERCEPATAN PROGRAM PTSL PADA BPN KABUPATEN KEDIRI - Toni Agus Supono; Eka Askafi (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Land dispute cases are still common in Indonesia, this problem is what makes the government really think of the best solution to avoid such social conflicts. That is why, the management of land serotying as a basis for the legal force of land ownership became a priority in the presidential program of 2019 years. The program was realized in the acceleration program of complete systematic land registration. The Program proved to reduce the problem of land disputes and make Indonesia has agrarian spatial well. All that, not apart from the role of HR in BPN quality and the team that support the program. In order for the program to run properly, certain strategies are required so that objectives can be achieved. This research explains the strategy, influencing factors, and implementation of PTSL.